Comparison of seismic and geodetic strain rates at the margins of the Ordos Plateau, northern China. Issue 2 (14th October 2017) - Middleton, Timothy A; Parsons, Barry; Walker, Richard T
Summary: Differences between seismic and geodetic strain rates can highlight regions of potential seismic hazard. In China, many of the most devastating historical and recent earthquakes have occurred around the margins of the Ordos Plateau. We construct an earthquake catalogue for the region that covers the 700 yr period from 1315 to 2015, and is thought to be complete for events with M s > 6. We use Kostrov summations to determine a seismic strain rate tensor for each of the margins of the Ordos Plateau. We also use the latest campaign GPS data to calculate both a continuously varying geodetic strain rate field for the region and individual geodetic strain rate tensors for each of the plateau margins. We then compare our seismic and geodetic strain rate results to identify regions with seismic moment deficits and also calculate expected recurrence intervals from our geodetic moment rates. We find notable seismic strain rate deficits in northern Ningxia (to the west of the Ordos Plateau), in the Hetao and Linhe Grabens (to the north of the plateau), and in the Shanxi Grabens (to the northeast of the plateau). In the Weihe Graben (to the south of the plateau), although there is an overall seismic strain rate excess for the last 700 yr, there is some indication of relative quiescence for the last few centuries. Assuming no aseismic accommodation of deformation, these deficits indicate enhanced potential for large earthquakes in these regions in the future. Either temporal clustering of earthquakes or individual, large-magnitude events with long recurrence intervals could explain these patterns of moment release. Meanwhile, in southern Ningxia (to the southwest of the plateau) we find a seismic strain rate excess, indicating a likely lower level of seismic hazard in this region. In southern Ningxia and the Shanxi Grabens the pattern of strain suggested by the Kostrov summations is consistent with the geodetic strains. In northern Ningxia, the Hetao and Linhe Grabens, and the Weihe Graben—where there are fewer historical earthquakes and sparser GPS station coverage—the seismic and geodetic patterns of strain release are inconsistent.